2021
DOI: 10.1007/s00018-021-03909-4
|View full text |Cite
|
Sign up to set email alerts
|

IL-36 cytokines in inflammatory and malignant diseases: not the new kid on the block anymore

Abstract: The IL-36 family of cytokines were first identified in 2000 based on their sequence homology to IL-1 cytokines. Over subsequent years, the ability of these cytokines to either agonise or antagonise an IL-1R homologue, now known as the IL-36 Receptor (IL-36R), was identified and these cytokines went through several cycles of renaming with the current nomenclature being proposed in 2010. Despite being identified over 20 years ago, it is only during the last decade that the function of these cytokines in health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 107 publications
(140 reference statements)
0
24
0
1
Order By: Relevance
“…Whilst each of the IL-1 family members has been shown to have pro and anti-tumorigenic effects to date, IL-36-related studies to date have shown primarily anti-tumorigenic roles [ 31 , 36 ]. Given the complex divergent nature of IL-1 family members across many pathologies including cancers, it is of little surprise that IL-36R signalling may indeed have both pro- and anti- tumorigenic effects, especially in a complex disease such as CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst each of the IL-1 family members has been shown to have pro and anti-tumorigenic effects to date, IL-36-related studies to date have shown primarily anti-tumorigenic roles [ 31 , 36 ]. Given the complex divergent nature of IL-1 family members across many pathologies including cancers, it is of little surprise that IL-36R signalling may indeed have both pro- and anti- tumorigenic effects, especially in a complex disease such as CRC.…”
Section: Discussionmentioning
confidence: 99%
“…IL-36γ is crucial in the regulation of immune responses and chronic inflammatory and fibrotic disorders ( 11 , 14 , 16 ). However, little is known about its regulation and functions in the AT inflammation in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas IL-36a, -b, and -g trigger immune cell infiltration and inflammatory pathways through the activation of IL-36R, the IL-36Ra functions as an anti-inflammatory factor by inhibiting IL-36R signaling (11)(12)(13). IL-36 isoforms are expressed by a broad variety of tissues and multiple cell types with their ultimate effects depending on a fine balance of their concentrations, the cellular target or the phase and context of the disease (11,14,15). Therefore, IL-36 has been implicated in multiple diseases with an inflammatory component including psoriasis, inflammatory bowel diseases, arthritis and joint diseases, renal and pulmonary injuries and even cancer (14,16), but little information about the impact of IL-36 on obesity-associated inflammation exists (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have demonstrated that IL-36g is secreted through an unconventional secretory pathway type I, specifically through the P2X7R and GSDMD membrane pores in a mechanism dependent on LPS/ATP stimulation. As P2X7R/GSDMD have an important role in the secretion of IL-36g; thus, we believe that blocking these pores can be a novel therapeutic approach to limit IL-36 cytokines bioavailability in several autoimmune diseases, cancer, obesity, and chronic inflammatory pain, among others, and ameliorate symptoms, as has been proposed elsewhere (33,34).…”
Section: Discussionmentioning
confidence: 77%